Boreolimnus, a new leafhopper genus from northern North America, with a review of Cribrus Oman (Hemiptera, Cicadellidae, Deltocephalinae) - Joel H. Kits (ZooKeys)
The poorly known leafhopper species described as Deltocephalus (Laevicephalus) concinnus var. incisurus DeLong, 1926 previously had no accepted generic placement. It is here redescribed and placed in Boreolimnus gen. nov. in the tribe Paralimnini, as Boreolimnus incisurus (DeLong) comb. nov. Cribrus micmac Hamilton, 1987 is a junior syn. nov. of B. incisurus. Due to historic confusion, the species currently placed in Cribrus Oman, 1949 were also reviewed. Cribrus concinnus (Sanders & DeLong, 1917) is redescribed, and a lectotype is designated to clarify the application of the name. Deltocephalus plagus Ball & DeLong, 1926 and Laevicephalus shingwauki Beamer & Tuthill, 1934 are recognized as junior syn. nov. of C. concinnus, now the only recognized species in the genus.